EFEKTIFITAS SISTEM PEMBELAJARAN BLOK TRI WULAN PADA MATA PELAJARAN PRODUKTIF PROGRAM KEAHLIAN BANGUNAN SMKN 1 JAKARTA - Emirda Kurniawan; Dadang Suyadi; R Karsono (LPPM Universitas Negeri Jakarta, 2012)
This research purposed to find the effectiveness of productive course subject using Three-Months-Blocking learning system at SMKN 1 Jakarta majoring in technical construction drawing. Seen from many obstacles happened during the process Three-Months-Blocking learning system at SMKN 1 Jakarta, we were interested in examining the effectiveness of the Three-Months-Blocking learning system. The research duration is on April until June 2012. The survey method was taken into consideration to find the effectiveness of Three-Months-Blocking learning system. The population number is 54 students as well as the samples number. Sampling determination used was saturated sampling. The instrument involved was non test instrument (questionnaire). The questionnaire had 78 problems. The reliability of the questionnaire was 0.703. The research was descriptive method using qualitative approximation method, so the hypothesis was not tested. Based on the result, the effectiveness of productive course subject using Three-Months-Blocking learning system at SMKN 1 reached 58.26%. As the conclusion, the effectiveness of productive course subject using Three-Months-Blocking learning system at SMKN 1 Jakarta majoring in technical construction drawing had been successful since the beginning of July 2011 until the late of July 2012.